Integrated pest management approaches to minimize incidence of cashew stem and root borers (Plocaederus spp.) - Raviprasad, T.N.; Shivarama Bhat, P.; Sundararaju, D. (Journal of Plantation Crops, 2009)
Cashew (Anacardium occidentale L.) trees infested by cashew stem and root borers (Plocaederus spp.) were treated with insecticides, entomopathogenic fungal spawn and neem oil after extraction of the pest stages in such trees, to prevent fresh infestation; referred to as ‘post extraction prophylaxis’ (PEP). Chlorpyriphos (0.2%) was identified as the most feasible PEP treatment in extensive field trials. Treatment with either neem oil (5 %) swabbing or application of Metarhizium anisopliae spawn (250 g/ tree) were proved to be ineffective in minimizing pest reinfestation, being on par with untreated control. Adoption of phytosanitation by removing the infested trees having more than 50 % bark circumference damage was proved to considerably reduce the number of trees having fresh pest incidence during the subsequent years. The pest population in a given location and also the pest load in infested cashew trees could be drastically reduced by adopting regular phytosanitation.